2018
DOI: 10.1016/j.celrep.2018.07.108
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Somatic Genes by Selective Recruitment of HDAC3 by BLIMP1 Is Essential for Mouse Primordial Germ Cell Fate Determination

Abstract: Primordial germ cells (PGCs) are fate determined from pluripotent epiblasts. Signaling pathways and transcriptional regulators involved in PGC formation have been identified, but detailed molecular mechanisms of PGC fate determination remains poorly understood. Using RNAi screening, we identified histone deacetylase 3 (HDAC3) as a regulator of PGC formation. Hdac3 deficiency resulted in decreased nascent PGCs in vitro and in vivo, and somatic developmental genes were de-repressed by Hdac3 knockdown during PGC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…While PGCs themselves become refractory to the Bmp signalling environment, their survival and further development is thought to be critically dependent on the ability of the adjacent ExM to provide extrinsic trophic growth factors 52 . Recent in vitro experiments similarly suggest that the role of Smad1 signalling during PGCLC differentiation may be to generate somatic cells that function to promote PGCLC survival 53 . Likewise, we observe here in PGCLC aggregates localised pockets of BV + cells within p-Smad159 active regions.…”
Section: Discussionmentioning
confidence: 99%
“…While PGCs themselves become refractory to the Bmp signalling environment, their survival and further development is thought to be critically dependent on the ability of the adjacent ExM to provide extrinsic trophic growth factors 52 . Recent in vitro experiments similarly suggest that the role of Smad1 signalling during PGCLC differentiation may be to generate somatic cells that function to promote PGCLC survival 53 . Likewise, we observe here in PGCLC aggregates localised pockets of BV + cells within p-Smad159 active regions.…”
Section: Discussionmentioning
confidence: 99%
“…BLIMP1 mediates its role as a transcriptional repressor through the recruitment of epigenetic regulators, which include histone deacetylases HDAC1/2/3, histone methyltransferases G9A (EHMT2) and EZH2, as well as the histone demethylase LSD1, and the protein arginine methyltransferase PRMT5 (26,30,31,32,33,34,35,36). Among these, the combination of HDACs and histone methyltransferases provide the potential to convert the epigenetic state of target genes from an open to repressed chromatin state, with recruitment of G9A and EZH2 providing the capacity to mediate the establishment of repressive methylation marks at H3K9 and H3K27 residues (26,33,37,38).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that selective recruitment of HDAC3 to somatic genes by BLIMP1 and subsequent repression of somatic gene expression are crucial for PGC fate determination ( Fig. 1) (Mochizuki et al, 2018).…”
Section: Introductionmentioning
confidence: 75%
“…We have recently established an efficient RNAi screening protocol to identify genes involved in PGC fate determination using PGCLC induction of mouse embryonic stem cells (ESCs) in culture (Mochizuki et al, 2018), and identified SETDB1 histone H3K9 tri-methyltransferase as a promising candidate. Setdb1 is constitutively expressed in epiblasts, PGCs, epiblast-like cells (EpiLCs) and PGCLCs ( Fig.…”
Section: Setdb1 Deficiency Represses Pgc Formationmentioning
confidence: 99%
See 1 more Smart Citation